The Death of Honi the Circle Maker - Ron, Zvi (The review of rabbinic Judaism, 2017)
Ancient literature preserves two accounts of the death of Honi the Circle Maker. One is in Josephus, where Honi is murdered by Jews after failing to participate in the Hasmonean civil war; the other is found in B. Ta. 23a, where Honi prays for death when nobody recognizes him after he awakes from sleeping for seventy years. While these two accounts seem to have no relation to each other, upon comparing the Bavli story to other tales of saintly long sleepers it appears that the Bavli story is a negative twist on the classic plot. The Bavli story is now understood as an aggadic version of the Josephus story, in the same category as the Bar Kamtza story and other similar explanatory narratives meant to highlight the reasons for tragedies in Jewish history.